Relationship CSR and employee commitment: Mediating effects of internal motivation and trust - Halder Yandry Loor-Zambrano; Luna Santos-Roldán; Beatriz Palacios-Florencio (European Research on Management and Business Economics (ERMBE), 2022)
Asbtract Purpose the main objective of this article is to check whether the relationship between corporate social responsibility activities and employee commitment is mediated by the existence of two other attitudinal variables of workers: intrinsic motivation and trust towards the organisation. Design/methodology/approach a survey of 318 Ecuadorian workers provides data that allows the application of structural equation modelling to verify the existence of such relationships. Findings the work shows a positive and significant relationship between CSR actions and the two attitudes of the employees considered: trust and intrinsic motivation. Furthermore, the mediating character that both variables play in the relationship between CSR and organisational commitment is confirmed. Ecuadorian managers can infer from this study the positive effects that CSR practices have on various attitudes and behaviors of employees, such as their motivation at work, their confidence in the company and their commitment to it. Research limitations/implications the scant generalisation of its results to the Ecuadorian reality given that the firms are located in a single zone of the country and belong to a specific activity. Practical implications new determinant factors of the relations between the endogenous and exogenous variables could be included. Social implications the consideration of other variables which could condition the relations studies: sex, age, etc. Originality/value the work increases the already existing knowledge about the relationship between CSR and different attitudes and behaviours of employees within formal work organisations.
Keywords: J24; M12; M14; M52; M54; 650; corporate social responsibility; Ecuador; employee commitment; formal organization; intrinsic motivation; trust towards the company